Measuring the Performance of Attention Networks with the Dalhousie Computerized Attention Battery (DalCAB): Methodology and Reliability in Healthy Adults - Jones, Stephanie A. H.; Butler, Beverly C.; Kintzel, Franziska; Johnson, Anne; Klein, Raymond M.; Eskes, Gail A. (Frontiers in Psychology, 2016)
Attention is an important, multifaceted cognitive domain that has been linked to three distinct, yet interacting, networks: alerting, orienting, and executive control. The measurement of attention and deficits of attention within these networks is critical to the assessment of many neurological and psychiatric conditions in both research and clinical settings. The Dalhousie Computerized Attention Battery (DalCAB) was created to assess attentional functions related to the three attention networks using a range of tasks including: simple reaction time, go/no-go, choice reaction time, dual task, flanker, item and location working memory, and visual search. The current study provides preliminary normative data, test-retest reliability (intraclass correlations) and practice effects in DalCAB performance 24-h after baseline for healthy young adults (n = 96, 18–31 years). Performance on the DalCAB tasks demonstrated Good to Very Good test-retest reliability for mean reaction time, while accuracy and difference measures (e.g., switch costs, interference effects, and working memory load effects) were most reliable for tasks that require more extensive cognitive processing (e.g., choice reaction time, flanker, dual task, and conjunction search). Practice effects were common and pronounced at the 24-h interval. In addition, performance related to specific within-task parameters of the DalCAB sub-tests provides preliminary support for future formal assessment of the convergent validity of our interpretation of the DalCAB as a potential clinical and research assessment tool for measuring aspects of attention related to the alerting, orienting, and executive control networks.